Strontium‐substituted biphasic calcium phosphate microspheres promoted degradation performance and enhanced bone regeneration - Chen, Ying; Liu, Zhongning; Jiang, Ting; Zou, Xinyu; Lei, Lei; Yan, Wenjuan; Yang, Jingwen; Li, Bo (Journal of biomedical materials research. Part A, 2020)
Biphasic calcium phosphate (BCP) ceramics are the subject of much attention for use as bone replacement material. However, it remains a challenge to promote the degradation and osteoinductivity performances of BCP ceramics. In this work, novel BCP ceramic microspheres with good degradation and excellent osteoinductivity were prepared through high‐content strontium (Sr) doping. The in vitro results indicated that the Sr10‐BCP, Sr40‐BCP, and Sr80‐BCP microspheres all had their HA crystals partially transformed to the beta tricalcium phosphate phase following high‐temperature sintering because of Ca‐deficient HA formed by the partial substitution of Ca ions by Sr ions. In addition, the degradation rate was increased with the doping of increasing amounts of Sr. All prepared microspheres enhanced human bone marrow‐derived mesenchymal stem cells attachment and proliferation. Specifically, among these modified microspheres, the Sr40‐BCP microspheres showed the highest osteogenic potential. Furthermore, Sr40‐BCP and HA microspheres were implanted in a calvarial defect model of rat to evaluate the in vivo bone augmentation ability. The results indicated that Sr40‐BCP microspheres degraded more completely and significantly promoted new bone regeneration compared with HA microspheres. In conclusion, Sr40‐BCP microspheres have excellent potential for degradation and bone regeneration and are promising osteogenic materials.